PENGARUH BEBAN KERJA BERLEBIH, STRESS KERJA, DAN KEPUASAN PENILAIAN KINERJA TERHADAP WORK-FAMILY CONFLICT PADA TENAGA KESEHATAN RSU DARMAYU PONOROGO - Ningtiyas, Feby Ayu; Chamidah, Siti; Riawan, Riawan (Bussman Journal : Indonesian Journal of Business and Management, 2022)
Work and family are two important aspects that cannot be separated. both to go hand in hand and need balance. Therefore, individuals who have families and work to be able to balance family members and also as workers. The purpose of this study was to examine the effect of the variables of excessive workload, work stress, and satisfaction on work-family conflict in the health workers of Darmayu Ponorogo General Hospital. The method used in this study is a quantitative method. The sampling technique in this study used a probability sampling technique, namely using a simple random sampling technique. The data used are primary data and data collection through questionnaires distributed to research subjects as many as 104 health workers at Darmayu Ponorogo General Hospital. This study resulted in a partial test (t) as follows: excessive workload (X1) = 0.046, work stress (X2) = 0.037, and performance satisfaction (X3) = 0.034. With the F test value (simultaneous) of 8,840